PENGELOLAAN DAN PEMANFAATAN SUMBER DAYA ALAM DALAM PERSPEKTIF EKONOMI ISLAM - Iqbal Iqbal (Al-Hisab: Jurnal Ekonomi Syariah, 2020)
ABSTRACT The Qur'an has provided a very clear concept related to the sustainable management and utilization of natural resources by paying attention to the natural surroundings. Humans are sent to earth as caliphs which are a manifestation of the nature of God, namely the Sustainer of Nature (Rabbul 'Alamin). Islam has provided a clear concept in natural resource management, such as the concept of ihyaul mawat or reviving the dead land and al imar or the prosperity of the surrounding environment. This concept is one of the recommendations of Islam to be able to utilize natural resources as a requirement in Islamic teachings. ABSTRAK Alquran telah memberikan konsep yang sangat jelas terkait dengan pengelolaan dan pemanfaatan sumber daya alam yang berkesinambungan dengan memperhatikan alam sekitar. Manusia diutuskan ke bumi sebagai khalifah yang merupakan manifestasi dari sifat Tuhan yang Mulia yaitu Pemelihara Alam (Rabbul „Alamin). Islam telah memberikan konsep yang jelas dalam pengelolaan sumber daya alam, seperti konsep ihyaul mawat atau menghidupkan lahan mati dan al imar atau memakmurkan alam sekitar. Konsep tersebut merupakan salah satu anjuran Islam untuk dapat memanfaatkan sumber daya alam sebagai tuntutan dalam ajaran Islam. Kata Kunci: Sumber Daya Alam, Ekonomi Islam, Ihyaul Mawat